Composition and nematicidal activity of the essential oil from Piper longum against root knot nematode - KUMAR, VIJAY; MONDAL, PARTHA CHANDRA; KUMAR, RAKESH; PANKAJ; KAUSHIK, PARSHANT; SHAKIL, NAJAM AKHTAR; GOWDA, A P ABHISHEK; RANA, VIRENDRA SINGH (The Indian Journal of Agricultural Sciences, 2023)
Piper longum L. (Piperaceae family), commonly known as long pepper, is used in traditional medicine and in recognized system of medicine in India for the treatment of inflammation, pain, epilepsy, arthritis, cancer, ulcer, and asthma in addition to pest control activity. Its fruits are rich in essential oil and possess different biological activities, but oil is not much explored against the root-knot nematodes. Thus, the essential oil from the fruits of P. longum was isolated by hydrodistillation method and analyzed by Gas chromatography-Flame ionisation detector and Mass spectrometry. Analysis showed that the oil is a complex mixture of volatile compounds. (Z)-β-Farnesene (25.08%), β-Caryophyllene (13.57%), α-Humulene (13.37%), 8-Heptadecene (9.28%), Heptadecane (7.07%), α-Patchoulene (5.44%), 3-Heptadecene (5.09%), γ-Elemene (4.37%), β-Humulene (3.69%) and Terpinen-4-ol (1.74%) were identified as main compounds in its oil. The essential oil was evaluated for its nematicidal activity against root-knot nematode at 62.5–1000 ppm concentrations in vitro conditions during 2020–21 at ICAR-Indian Agricultural Research Institute, New Delhi. Results showed promising nematicidal activity of the oil and have caused mortality of juvenile (J2), ranging from 2.33–88.0% after 24–96 hours of treatment compared to untreated control. The oil was further evaluated under the pot conditions in tomato (Solanum lycopercicum L.) (var. Pusa Ruby) at 3000 and 2000 ppm. Results showed a significant reduction in the number of galls/root of tomato with better plant growth in the essential oil based treatment as compared to the untreated control. These results suggest that the oil can be used for the development of nematicidal product for the protection of crops from the infestation of M. incognita.